THE EFFECT OF TRAINING, WORK MOTIVATION, AND WORKLOAD ON THE PERFORMANCE OF HOSPITAL EMPLOYEES - YunataKandhias Akbar; MohdHaizam Saudi; Obsatar Sinaga (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to analyze the effects of training, work motivation, and workload on performance employees. This study was conducted at Harapan Kita Cardiovascular Hospital (RSJPDHK). The population used in this study is all of the administrative staff at Harapan Kita Heart and Blood Vessel Hospital (RSJPDHK). The sample was collected to determine a probability sampling method with a random sampling technique with Slovin function, then determined a sample of 140 respondents. The measurement of variables uses Likert scale. Data collection used a survey method and using a questionnaire, for then analyzed with linear regression technique.The result shows that: training, work motivation, and workload has a positive effect on the performance employees of simultaneously, and training, work motivation has a positive effect on the performance employees of partially, and workload doesn't have an effect on the performance employees of partially.